Harry Potter y el prisionero de Azkaban = Harry Potter and the prisoner of Azkaban / translated by Adolfo Munoz Garcia y Nieves Martin Azofra - Rowling, J. K. (Rowling, J. K. Silsilat Hārī Būtir, 1999)
During his third year at Hogwarts School for Witchcraft and Wizardry, Harry Potter must confront the devious and dangerous wizard responsible for his parents' deaths.